2018
DOI: 10.3390/molecules23112869
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ligand Functionalization of UiO-66-Based Metal-Organic Frameworks When Used as Sorbents in Dispersive Solid-Phase Analytical Microextraction for Different Aqueous Organic Pollutants

Abstract: Four metal-organic frameworks (MOFs), specifically UiO-66, UiO-66-NH2, UiO-66-NO2, and MIL-53(Al), were synthesized, characterized, and used as sorbents in a dispersive micro-solid phase extraction (D-µSPE) method for the determination of nine pollutants of different nature, including drugs, phenols, polycyclic aromatic hydrocarbons, and personal care products in environmental waters. The D-µSPE method, using these MOFs as sorbents and in combination with high-performance liquid chromatography (HPLC) and diode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…A step forward in ensuring the true expansion of MOFs as competitive materials for D-µSPE requires not only the assurance of a better performance than that resulting from commercial materials (exhaustive comparison and inter-laboratory validation) [5,10], but also deep evaluation of the main factors of MOFs justifying the improved analytical performance for target compounds [11,12]. Gaining an understanding of the process can serve as the basis of proper MOF design.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A step forward in ensuring the true expansion of MOFs as competitive materials for D-µSPE requires not only the assurance of a better performance than that resulting from commercial materials (exhaustive comparison and inter-laboratory validation) [5,10], but also deep evaluation of the main factors of MOFs justifying the improved analytical performance for target compounds [11,12]. Gaining an understanding of the process can serve as the basis of proper MOF design.…”
Section: Introductionmentioning
confidence: 99%
“…Lirio et al also pointed out the influence of the metal, particularly the radius of the metal [13]. Taima-Mancera et al showed the positive effects of incorporating polar functionalities in the organic ligand of the MOFs used in D-µSPE when intending to extract polar analytes of a small size [12], with this idea having been further expanded by Boontongto et al to other application studies for polar analytes [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we take into consideration the idea of avoiding the use of heavy metals when designing MOFs, it is clear that many MOFs included in Table 2 present non-toxic metallic ionic centers [54,65], such as Zn 2+ [93], Zr 4+ [82] or Al 3+ [54]. Regarding the synthetic solvents in MOFs preparations, most studies employ DMF [82,90,94], avoiding in this way toxic chlorinated ones, such as dichloromethane or chloroform. Furthermore, the DMF volumes required are usually low (around 30 mL for 15 mg of MOF).…”
Section: Mofs In Analytical Sample Preparationmentioning
confidence: 99%
“…In general, quite low amounts of MOF as sorbents are always needed [54,82,84] in all microextraction procedures listed, from 2 mg [80] to 60 mg [89]. Regarding extraction times, there are reported values around 3 min or even less [85] for µ-dSPE and some of its applications in the magnetic variant [89,91].…”
Section: Mofs In Analytical Sample Preparationmentioning
confidence: 99%